Bullous pemphigoid in a patient with psoriasis after mRNA COVID‐19 vaccination. Issue 1 (8th December 2022) - Merilleno, Arbie Sofia P.; Quizon, Mae R.; Legaspi, Kristine Natalee M.
Abstract: Bullous pemphigoid and psoriasis are two well‐characterised chronic autoimmune diseases that may be triggered by drugs, infections or vaccines. The coexistence of the two is a rare event but is more extraordinary if incited by messenger RNA (mRNA) COVID‐19 vaccination. A 62‐year‐old Filipino male experiencing a flare‐up of his long‐standing psoriasis vulgaris presented with new onset tense blisters on the legs 2 days after his first booster dose of mRNA (Pfizer‐BioNTech) vaccination. The clinical, skin punch biopsy, direct immunofluorescence and enzyme‐linked immunosorbent assay were consistent with bullous pemphigoid. Complete resolution of the vesicles and bullae with no new lesions and flattening of psoriasis plaques were observed after 1 month of treatment of systemic corticosteroids and corticosteroid‐sparing agents. An association may exist between bullous pemphigoid development and mRNA COVID‐19 vaccination.